Does paternal immunocompetence affect offspring vulnerability to maternal androgens? A study in domestic chickens - Asmoro Lelono; Diana A. Robledo-Ruiz; Tom V. L. Berghof; Henk K. Parmentier; Bernd Riedstra; Ton G. Groothuis (Biology Open, 2019)
Exposure of yolk androgens can positively stimulate chick growth and competitive ability, but may negatively affect immunity. It has been hypothesized that only chicks from immunologically superior fathers can bear the cost of prenatal exposure to high androgen levels. To test this hypothesis, we paired roosters from two selection lines, one up- and one down-selected for natural antibodies (NAbs), with hens from a control line. We measured yolk testosterone and androstenedione levels, and we injected the treatment group of eggs of each female with testosterone suspended in sesame oil and the control group with sesame oil only. We then measured hatching success and growth, and characterized the humoral and cellular immune responses using three different challenges: a phyto-hemagglutinin, a lipopolysaccharide and a sheep red blood cell challenge. We found that the hatching success, body mass, initial levels of natural antibodies and the chicks’ immunological responses to the three different challenges and development were affected neither by paternal immunocompetence nor by treatment. These results do not support the hypothesis that chicks from low-NAb line fathers are more sensitive to testosterone exposure during embryonic development than chicks from high-NAb line fathers.